Interview with Lance Taylor: 'Wage repression and secular stagnation are rather close in kind' - Lance Taylor; Marc Lavoie (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
Lance Taylor received a BS degree with honours in mathematics from the California Institute of Technology in 1962 and a PhD in Economics from Harvard University in 1968. He has been a professor in the economics departments of Harvard and the Massachusetts Institute of Technology, among other research institutions. He is currently the Arnhold Professor Emeritus of International Cooperation and Development at the New School for Social Research, New York. He has published widely in the areas of macroeconomics, development economics and economic theory.
Keywords: 330